Recent acute prerace systemic illness in runners increases the risk of not finishing the race: SAFER study V - Gordon, L.; Schwellnus, M.; Swanevelder, S.; Jordaan, E.; Derman, W. (British Journal of Sports Medicine, 2017)
Aim: There are limited data on the negative effects of exercise in athletes with acute infective illness. The aim of this study was to determine whether a recently diagnosed prerace acute illness in runners affects the ability to finish a race.